2008
DOI: 10.1002/mar.20220
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of framing effects in negotiations: A study of single‐family home sales

Abstract: This paper integrates Prospect Theory and the concept of framing in a study of consumer negotiated pricing in a real estate context. Building on previously conducted experimental designs, a field survey indicated that home sellers using sales price as a reference point display greater willingness to make concessions than those who use equity as their reference point. Further, the third-party influence of the realtor was shown to alter Prospect Theory predictions so that even equity-based sellers became concess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…We thus expect stickiness to reflect a market correction, in which sellers in the long duration/gain and short duration/loss conditions realized their initial prices were too high, and quickly correct for their pricing errors. Indeed, recent research on the housing market has shown that when home sellers use comparable sale prices as a reference point they are likely to make price concessions [35]. Consequently, we expect our predictions related to initial asking price to reverse as sellers are forced to correct their prices:…”
Section: Financial Reference Point and Ownership Duration Effectsmentioning
confidence: 94%
See 1 more Smart Citation
“…We thus expect stickiness to reflect a market correction, in which sellers in the long duration/gain and short duration/loss conditions realized their initial prices were too high, and quickly correct for their pricing errors. Indeed, recent research on the housing market has shown that when home sellers use comparable sale prices as a reference point they are likely to make price concessions [35]. Consequently, we expect our predictions related to initial asking price to reverse as sellers are forced to correct their prices:…”
Section: Financial Reference Point and Ownership Duration Effectsmentioning
confidence: 94%
“…While we predicted a reversal of this relationship on stickiness when considering financial gains and losses, we do not expect a similar reversal in the domain of emotional gains and losses. In the domain of financial gains and losses, the reversal on price stickiness reflects a correction in which sellers confront marketplace realities in the form of comparable selling prices [35]. In the case of emotional gains and losses, there is no objective external reference point that can guide sellers in their pricing.…”
Section: Emotional Reference Point and Ownership Duration Effectsmentioning
confidence: 99%
“…For example, Bazerman and colleagues (1985) found that negotiators who had a gain frame adopted less risky strategies and reached more agreements and better outcomes than negotiators with a loss frame. In contrast, loss frames have been found to lower concession making, produce more contentious behavior, increase the likelihood of an impasse, and reduce the number of agreements reached in negotiations (Bottom, 1998;De Dreu, Carnevale, Emans, & Van de Vliert, 1994;Kristensen & Gärling, 1997b;Neale, Huber, & Northcraft, 1987;Witte, Grünhagen, & Gentry, 2008).…”
Section: Negotiator Cognitionmentioning
confidence: 98%
“…Prospect theory, in general, and the reflection effect, in particular, have been shown to be quite robust across a wide range of applications (e.g., Cain, Law, & Peel, 2008;Forlani, 2002;Kalwani et al, 1990;Lee, 1994;Kameda & Davis, 1990;Myagkov & Plott, 1997;Olsen, 1997;Puto, 1987;Qualls & Puto, 1989;Schmidt & Zank, 2008;Thaler, 2008;Witte, Grunhagen, & Gentry, 2008). Yet findings regarding the application of prospect theory to time have been mixed.…”
Section: The Application Of Prospect Theory To Time-related Decisionsmentioning
confidence: 99%